Nature Themed English Songs for Language Learning and Environmental Awareness in Preschoolers - Pratiwi Lestari; Nurul Aryanti; Welly Ardiansyah; Vasa Annisa Indina (Universitas Pahlawan Tuanku Tambusai, 2026)
Songs are widely recognized as effective instructional media for young learners because they encourage active engagement, support vocabulary development, and create meaningful learning experiences. Nevertheless, research focusing on the implementation of nature-themed English songs in Indonesian preschool EFL settings remains limited. Therefore, this study aimed to examine the effectiveness of nature-themed English songs in improving preschool students’ language learning and environmental awareness. The study applied a pre-experimental one-group pretest-posttest design involving 21 preschool students at a PAUD institution in Palembang, Indonesia. Data were collected through vocabulary and pronunciation tests, observation checklists, and environmental awareness checklists. The results showed a significant improvement in students’ language performance and environmental awareness after the treatment. The mean score increased from 57.28 on the pre-test to 84.52 on the post-test, supported by a significant t-test result (p 0.05). In conclusion, nature-themed English songs were found to be effective in enhancing preschool students’ English language learning.